Turkish–British relations in the 1930s: from ambivalence to partnership. Issue 5 (3rd September 2018) - Barlas, Dilek; Gülmez, Seçkin Barış
ABSTRACT: This article seeks to explain how Britain and Turkey established a partnership in the second half of the 1930s despite the fact that they failed to agree upon a common rival to stand against. The prevailing International Relations literature highlights the existence of a common enemy as an essential component of alliance formation in world politics. The paradox underlying the British–Turkish partnership was the absence of a common enemy, since Britain was mainly disturbed by the revisionist policies of Germany, while Turkey was threatened by Italy's aggressive policy over the Mediterranean. In this respect, the article will first discuss how the academic literature explains the essential components of alliance formation in international relations. The second section will discuss in detail how British and Turkish threat perceptions diverged emphasizing the lack of a common rival. The final section will discuss how a bilateral partnership was successfully forged despite the absence of a common rival. Overall, the article argues that Britain and Turkey formed a partnership without a common enemy, as they shared a common fear of abandonment, i.e. the fear of losing an actual or a potential ally to an enemy.